Outcomes in patients with early-onset fetal growth restriction without fetal or genetic anomalies. (18th August 2019) - Gupta, Simi; Naert, Mackenzie; Lam-Rachlin, Jennifer; Monteagudo, Ana; Rebarber, Andrei; Saltzman, Daniel; Fox, Nathan S.
Abstract: Objective: Early-onset fetal growth restriction is associated with poor pregnancy outcomes, but frequently is due to fetal structural or chromosomal abnormalities. The objective of this study was to determine outcomes in patients with early-onset fetal growth restriction without diagnosed fetal or genetic anomalies and to identify additional risk factors for poor outcomes in these patients. Methods: This was retrospective cohort study of singleton pregnancies in women with early-onset growth restriction defined as a sonographic estimated fetal weight <10% diagnosed between 16–28 weeks' gestation. We excluded all women with a fetal structural or chromosomal abnormality diagnosed prenatally. Data on pregnancy characteristics and outcomes were collected and analyzed for estimated fetal weight <10% and ≤5%. A nested case-control study within the cohort of patients with ongoing pregnancies was then performed to identify risk factors associated with poor pregnancy outcome using chi-squared test. Results: One hundred forty-two patients were identified who met inclusion and exclusion criteria and 20 patients were found to have fetal structural or chromosomal abnormalities. In the remaining 122 patients, the incidence of intrauterine fetal demise was 5.7% and there were high rates of preterm birth <37 weeks (20%), birth weight <10% (59.3%), and gestational hypertension (14.1%). Later gestational age at diagnosis and the presence of echogenic bowel and abnormal initial umbilical artery Dopplers were associated with poor pregnancy outcome (22.56 versus 20.86 weeks, p  = .046), (17.4 versus 2.2%, OR 9.68, 95%CI 1.65–56.73), and (35.3 versus 0%, OR 4.46, 95%CI 2.65–7.50) respectively. Conclusions: Patients with early-onset fetal growth restriction with no fetal structural or genetic abnormality have a high risk of poor pregnancy outcomes. Gestational age at diagnosis and certain ultrasound findings are associated with poor pregnancy outcome.